Harnessing Solar Cell and Radio Wave Integration: A Game-Changer for AI and Business - Bimalendu Pendy (Information Technology and Science (ITScience), 2023)
Solar cells, radio waves, artificial intelligence (AI), and commerce are coming together to provide a novel combination of cutting-edge technology, wireless communication, and sustainable energy. This article examines the many facets of this integration's consequences, ranging from the fundamentals of radio waves and solar cells to the evolution of artificial intelligence and corporate processes. By fostering environmental responsibility, cutting energy costs, and improving AI-driven sustainability, the integration puts enterprises at the forefront of environmental responsibility and sustainability initiatives. Even if there are still issues with technological complexity, cost, and regulatory compliance, there are a lot of potential, including those related to smart cities, telecoms, electric cars, and energy-efficient buildings. This convergence could lead to the disruption of established sectors, a decrease in carbon emissions, and increased innovation in AI applications. Research and development to maximize productivity and investigate new market prospects, industrial upheavals, and environmental effects are some of the future directions that will be pursued. In order to accelerate innovation and adoption globally and, eventually, transform the way we communicate, generate energy, and do business in a world that is increasingly linked and sustainable, collaboration and partnerships are crucial.